Evolution and current status of the work developed within the OECD regarding the taxation of the digital economy - Huaylla Hernández, Nátali (2022)
This article will focus on providing a brief recount of the documents, on a global and digital scope, for its adoption by the various signatory countries this very year, released under the parameters of the OCDE about the upgrading of the international taxation laws, specifically the BEPS 2.0.